Predicting Outcome in Postanoxic Coma: Are Ten EEG Electrodes Enough?. Issue 3 (May 2017) - Tjepkema-Cloostermans, Marleen C.; Hofmeijer, Jeannette; Hom, Harold W.; Bosch, Frank H.; van Putten, Michel J. A. M.
Abstract : Introduction: Increasing evidence supports that early EEG recordings reliably contribute to outcome prediction in comatose patients with postanoxic encephalopathy. As postanoxic encephalopathy typically results in generalized EEG abnormalities, spatial resolution of a small number of electrodes is likely sufficient, which will reduce set-up time. Here, the authors compare a reduced and a 21-channel EEG for outcome prediction. Methods: EEG recordings from 142 prospectively collected patients with postanoxic encephalopathy were reassessed by two independent reviewers using a reduced (10 electrodes) bipolar montage. Classification and prognostic accuracy were compared with the full (21 electrodes) montage. The full montage consensus was considered Gold Standard. Results: Sixty-seven patients (47%) had good outcome. The agreement between the individual reviewers using the reduced montage and the Gold Standard score was good (κ = 0.75–0.79). The interobserver agreement was not affected by reducing the number of electrodes (κ = 0.78 for the reduced montage vs. 0.71 for the full montage). An isoelectric, low-voltage, or burst-suppression with identical bursts pattern at 24 hours invariably predicted poor outcome in both montages, with similar prognostic accuracy. A diffusely slowed or normal EEG pattern at 12 hours was associated with good outcome in both montages. Conclusions: Reducing the number of electrodes from 21 to 10 does not affect EEG classification or prognostic accuracy in patients with postanoxic coma.